2009
DOI: 10.1063/1.3149788
|View full text |Cite
|
Sign up to set email alerts
|

Langevin thermostat for rigid body dynamics

Abstract: We present a new method for isothermal rigid body simulations using the quaternion representation and Langevin dynamics. It can be combined with the traditional Langevin or gradient (Brownian) dynamics for the translational degrees of freedom to correctly sample the canonical distribution in a simulation of rigid molecules. We propose simple, quasisymplectic second-order numerical integrators and test their performance on the TIP4P model of water. We also investigate the optimal choice of thermostat parameters. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
258
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(258 citation statements)
references
References 23 publications
0
258
0
Order By: Relevance
“…To sample equilibrium thermodynamics, we employ Virtual Move Monte Carlo (VMMC), 38,39 an efficient Monte Carlo algorithm which moves clusters of interacting particles. For kinetic results, we use the rigid-body Langevin Dynamics (LD) algorithm of Davidchack et al 40 Langevin algo-rithms both reproduce the diffusive motion of particles and sample from the equilibrium ensemble.…”
Section: Methodsmentioning
confidence: 99%
“…To sample equilibrium thermodynamics, we employ Virtual Move Monte Carlo (VMMC), 38,39 an efficient Monte Carlo algorithm which moves clusters of interacting particles. For kinetic results, we use the rigid-body Langevin Dynamics (LD) algorithm of Davidchack et al 40 Langevin algo-rithms both reproduce the diffusive motion of particles and sample from the equilibrium ensemble.…”
Section: Methodsmentioning
confidence: 99%
“…For oxDNA, thermodynamic averages are typically calculated using the Virtual Move Monte Carlo (VMMC) algorithm. 162,194 Dynamical studies reported in this work use a Langevin Dynamics (LD) algorithm for rigid bodies, 163 which samples from the Boltzmann distribution and generates diffusive particle motion.…”
Section: Discussionmentioning
confidence: 99%
“…These forces are chosen so that particles move diffusively and the system samples from the Boltzmann distribution. The kinetic results reported in this work were obtained using the quaternion-based algorithm for rigid bodies of Davidchack et al 163 Other work on oxDNA has been performed with an Andersen-like thermostat.…”
Section: Langevin Dynamicsmentioning
confidence: 99%
“…This model treats some parts of polymer as rigid bodies and phenomenologically introduces the effects of ignored degrees of freedom by the friction and fluctuation terms. Numerical efficiencies have been investigated for some rigid body Langevin simulations [3,4,10]. The mathematical formal structure of Eq.…”
Section: Analyses Of Coarse Grained Equation Of Motion For Systems Hamentioning
confidence: 99%
“…Recent interests are mainly focused on the simulation procedure which is efficient to reach equilibrium condition by introducing the effects of thermal bath. The Langevin-type equations of motion can be accepted as an efficient and stable method for finding thermal equilibrium in the atomistic molecular dynamics simulations [3,4]. Unfortunately most of all the previous numerical studies like ones mentioned above are based on the phenomenologically introduced equation of motions and then the bases of the theoretical backgrounds are not sufficient for constructing the multiscale-simulation procedures for inhomogeneous structured materials.…”
Section: Introductionmentioning
confidence: 98%